Comparative analysis of clinicopathological characteristics of central necrotizing breast cancer and basal cell-like breast cancer - Ding, Li; Kun, Wang; Xu, Wenjing; Chen, Shaohua; Cai, Zhaogen (Frontiers in Oncology, 2023)
Purpose: To compare the clinicopathological and immunohistochemical characteristics of centrally necrotizing carcinoma of the breast (CNC) and basal-like breast cancer (BLBC) and analyze the characteristics of molecular typing of the CNC. Methods: The clinicopathological features of 69 cases of CNC and 48 cases of BLBC were observed and compared. EnVision immunohistochemical staining was performed to detect the expressions of hypoxia-inducible factor 1α (HIF-1α), Breast cancer susceptibility gene 1 (BRCA1), and vascular endothelial growth factor (VEGF) in CNC and BLBC. Results: The age of 69 patients ranged from 32 to 80 years, with an average of 54.55 years. Gross observation showed that most tumor was a well-defined single central nodule, with a diameter of 1.2 5.0 cm and. Microscopically, there is a large necrotic or acellular area in the center of the tumor, mainly composed of tumor coagulative necrosis with varying degrees of fibrosis or hyaline degeneration. A small amount of cancer tissue remained around the necrotic focus in ribbon or small nest shape. Among 69 cases of CNC, the proportion of basal cell type (56.5%) was significantly higher than that of lumen type A (18.84%), and lumen type B (13.04%). HER2 overexpression (5.8%) and non-expression (5.8%). 31 cases were followed up for 8 50 months, with an average of 33.94 months. 9 cases of disease progression. Compared with BLBC, protein expression of BRCA1 and VEGF was no significant differences in response to CNC (P > 0.05), and there were significant differences in protein expression of HIF-1α(P<0.05). Conclusion: The molecular typing of CNC showed that over half of those were BLBC. No statistically significant difference in the expressions of BRCA1 was observed between CNC and BLBC; thus, we predict that targeted therapy for BRCA1 in BLBC may also have considerable effects in CNC patients. The expression of HIF-1α is significantly different in CNC and BLBC, and perhaps HIF-1α can be used as a new entry point to distinguish between the two. There is a significant correlation between the expression of VEGF and HIF-1α in BLBC, and There was no significant correlation between the expression levels of the two proteins in CNC.